Divine envy, jealousy, and vengefulness in ancient Israel and Greece - Lasine, Stuart (Routledge, Taylor & Francis Group, 2023)
"This book is the first in-depth comparative analysis of envy, jealousy, and vengefulness experienced by divine personalities in the Hebrew Bible and ancient Greek texts, and the functions served by attributing negative emotions and traits to one's gods. Readers are informed about the vigorous debates concerning the nature of emotion, a field with rapidly growing interest, including the specific emotions of envy, jealousy, and vengefulness. The book charts the complex, multi-faceted presentation of divine beings in the Hebrew Bible and ancient Greek literature, including their negative emotions. While the detailed readings of key biblical and Greek texts can stand on their own, Lasine's comparative analyses allow readers to appreciate the uniqueness of each tradition. Finally, examining the functions served by envisioning one's God or gods as jealous, envious and vengeful offers readers a fresh perspective on biblical theology and the ways in which Greek poets and dramatists imagined the nature of their deities. Divine Envy, Jealousy, and Vengefulness in Ancient Israel and Greece is intended for biblical, classical, and literary scholars, as well as the general reader interested in the Hebrew Bible and/or ancient Greek literature"--